AVALIAÇÃO BIOMÉTRICA E ANÁLISE SANGUÍNEA DE BEZERROS DESTINADOS A PROVA DE LAÇO COMPRIDO - Piazzon, Cleiton José; Mendes, Dalton; Gregory, Marcos; Dias, Júlia; Castro, Waldyr; Escobar, Loraine (ANAIS DO ENIC, 2018)
-